PjBL-Based Flannel Board Media to Improve Number Skills of Group B Children - Maria Komang Oktavia Damayanti; Didit Pramunditya Ambara; I Wajan Sujana (Universitas Pendidikan Ganesha, 2025)
Young children often experience difficulties in maintaining focus when learning number concepts, which can lead to decreased interest in learning if the instructional approach is monotonous. One potential solution is to develop innovative learning media that attract children’s attention and facilitate their understanding of number concepts. This study aims to develop and evaluate the effectiveness of a flannel board-based Project-Based Learning (PjBL) media to enhance young children's numeracy skills. This research is a type of Research and Development (R&D) using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The research subjects involved three expert lecturers as validators and 25 group B children as respondents in product trials. Data were collected through observation and non-test observation questionnaires and analyzed using descriptive quantitative analysis and inferential statistical tests. The results showed that the flannel board-based PjBL media obtained a very good qualification in the validation test, good qualifications in individual and small group trials, and was effective in improving numeracy skills based on effectiveness testing. The conclusion of this study is that the flannel board-based PjBL media is feasible and effective for use in early childhood number learning. The implication of this research is that contextual media can serve as an alternative for teachers to create engaging number learning experiences beyond conventional textbooks and increase children’s active participation.